Bologna Process and teaching of Public Health in Poland - Stelmach, Włodzimierz; Zawadzka, Magdalena; Bąk, Ewa; Kowalska, Alina; Bryła, Marek (Polish Journal of Public Health, 2009)
Several European countries decided to adopt Bologna Declaration and expressed their positive attitude towards it. Thanks to their new statutes and law regulations we can see how governments were involved directly into modifi cation in Higher Education System in Europe. European Higher Education Institutions put an effort and had signifi cant infl uence on creating European Higher Education Area.The main aim of this paper is to present the idea of education within public health in Poland in the Bologna Process perspective. At the beginning of this paper we can fi nd the main stages of Bologna Process, from Sorbonne’s Declaration to London’s Conference. The next stage of this work is the description of the most important goals, Assumption and outlines for all countries involved directly in this policy. The signifi cance of introducing European Credit Transfer System (ECTS), Diploma Supplement and three-year-studies has been indicated. Next part of the paper presents the education system for Public Health. Finally, the defi niton of “Public Health” was created and its history described.The matter of future workers and their qualifi cations were also considered signifi cant issue. The last part of the text is about Polish Public Health Care Education System based on Bologna Process.